If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 5 = (x + -1) Reorder the terms: 5 + 5x = (x + -1) Reorder the terms: 5 + 5x = (-1 + x) Remove parenthesis around (-1 + x) 5 + 5x = -1 + x Solving 5 + 5x = -1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5 + 5x + -1x = -1 + x + -1x Combine like terms: 5x + -1x = 4x 5 + 4x = -1 + x + -1x Combine like terms: x + -1x = 0 5 + 4x = -1 + 0 5 + 4x = -1 Add '-5' to each side of the equation. 5 + -5 + 4x = -1 + -5 Combine like terms: 5 + -5 = 0 0 + 4x = -1 + -5 4x = -1 + -5 Combine like terms: -1 + -5 = -6 4x = -6 Divide each side by '4'. x = -1.5 Simplifying x = -1.5
| 2+2=7-3 | | 4-(8+2n)=-2(n+2) | | 9x^2-79x+56=0 | | -8x+24=0 | | 25x+5x-15=0 | | 9x-11=4x+6+5x+5 | | 9(m+2)+1=19+9m | | 5t+10=2t+31 | | 2x+4y+7=0 | | 21+2w=p | | 2x-2x+2=0 | | -2-3y=22 | | 5x=21+2a | | -x+4x=0 | | 3v+10=31 | | 4g+9=2g+17 | | Y=(-x)+8 | | -4x-2x-6=0 | | 2x+4=100000 | | 443x+8=11 | | Y=-12x | | -7x+9x+4=0 | | 6+4(3-k)=2(-2k+9) | | 12=3v-15 | | 8p-8=10-3p | | 5-2y=y | | 4x^2-9x+11=2x+5 | | 8x^3+24x-24x^2-8=0 | | 4x^2+24x+8=0 | | 2x^3+3x^2-12x-10=0 | | x^2+10x+39=-5x-5 | | 6k-5k+10-18= |